Quantitative Attribution of Runoff and Sediment Changes in the East River Basin and Impact on Erosion and Siltation of River Channel - LI Huadong; ZENG Jiali; PAN Yifei; ZHANG Li; LAI Zhigang (Renmin Zhujiang)
Under the disturbance of global warming and intensive human activities,runoff and sediment in the river basin have changed significantly,thus causing enormous ecological and environmental pressure in rivers,estuaries and coastal waters.Taking East River basin as the research object,this paper analyzes the temporal characteristics of runoff and sediment by M-K test and Pettitt test,quantitatively separates the impact of climate change and human activities on runoff and sediment in the river basin by the double mass curve method and modified SWAT model,and evaluates its effect on erosion and siltation of downstream river channel.Results show that:①SWAT model was suitable for the daily and monthly runoff and sediment simulations in the East River basin,with poor simulation for runoff and sediment with daily average discharges higher than 1 500 m3/s;②The change point of runoff and sediment was 1973 and 1988 respectively.Therefore,the baseline period for runoff was 1967—1973 and sediment was 1967—1988,while impact period was 2009—2016;③The impact of human activities on water and sediment changes in the basin is significant.Contribution of climate change and human activities for runoff in 2009—2016 was about 57% and 43% respectively.Climate change and population growth were the main contribution factors for annual runoff reduction.While human activities,especially dam construction,contributed over 90% of sediment.Population growth,soil and water conservation project,and dam construction in basin were the major factors for annual sediment reduction;④Affected by sand mining in river channel,after the baseline period,the impact of human activities,especially dam construction on the middle and lower channel was firstly decreased and then increased.During the impact period,the contribution of dam construction to the erosion and siltation of middle and lower river channel was 25.8%,which was not the main factor for the evolution of the middle and lower river channel.